Identification of Soil Damage Due to Biomass Production in Bekasi Regency, Indonesia - Hakim, Dani L; Adji, Riyanto; Satwhikawara, Rachmi; Alam, Syamsu (Universitas Pattimura, 2024)
The primary objective of this study was to determine the current condition, areas, and potential of soil degradation due to biomass production in Bekasi Regency. This study used a survey-based methodology that involved direct field observation and collection of soil samples from specified agricultural and forestry areas based on work maps. The laboratory analysis was conducted on the collected soil samples. The initial phase of soil damage determination involved an evaluation of the current soil condition. Soil condition maps were created utilizing data derived from the determination of key soil parameters based on the standard of so il damage criteria. The result of the analysis indicated that the degree of soil damage in Bekasi Regency due to biomass production varied from slight to moderate. The primary limiting factors were identified as soil permeability (p), redox potential (r), to tal porosity (v), electrical conductivity (e), bulk density (d), and pH level (a). The limiting factors were predominantly influenced by the constraints associated with the physical characteristics of the soil. The phenomenon is commonly associated with the high level of land exploitation, characterized by the use of chemical inputs, resulting in soil compaction. The process of compaction has a substantial impact on soil properties, including permeability, porosity, redox potential, bulk density, and electrical conductivity.